Impact of the Hunga Tonga-Hunga Ha'apai volcanic eruption on the changes observed over the Indian near-equatorial ionosphere. Issue 8 (15th October 2022) - Rakesh, V.; Haridas, Sreekumar; Sivan, C.; Manoj, M.G.; Abhilash, S.; Paul, Binu; Unnikrishnan, K.; Mohanakumar, K.; Sumesh Chandran, R.
Highlights: Ionospheric effects of AGWs of volcano explosion over near-equatorial site using 205 MHz VHF Radar. A bottom-side ESF irregularity echo with a plume-like structure noticed. Quasi-periodic oscillations in TEC and amplitude scintillations were observed. Concurrent observations by AWS network, GNSS receiver, and Swarm satellite confirms the findings. This work offers valuable insight into lower atmosphere-Ionosphere coupling. Abstract: The response of the Tonga volcanic eruption on the ionospheric F-region over the near-equatorial sector has been studied using the 205 MHz VHF radar at Cochin, Kerala, India. The Tonga eruption, a massive underwater volcanic event that occurred at Hunga Tonga-Hunga Ha'apai in the Pacific Ocean, started on 14th December 2021 and ended with a giant explosion on 15th January 2022. The internal gravity waves (IGWs) generated due to the eruption reverberated over the globe. The effect reached the ionosphere, creating spread-F irregularities. The activity was observed with the help of the 205 MHz VHF radar and other supporting instruments such as automatic weather station (AWS), Global Navigation Satellite System (GNSS) receiver, and Swarm Charlie (Swarm C) satellite. Enhanced surface pressure of 2 hPa was recorded at Cochin and adjoining areas due to the direct (i.e., wave along the shorter great circle path) gravity wave (GW) on 15th January. The shorter great circle path wave required 10 h 50 min to reach the Indian near-equatorial sector whereas, its antipodal counterpart wave (wave along the longer great circle path) reached Kerala on 16th January first as enhanced (0.54 hPa) and subsequently as reduced (0.8 hPa) surface pressure fluctuations. After the transit of IGWs on 15th January, a bottom-side F-region irregularity echo with a plume-like structure lasting for ∼ 4.5 h occurred between 276 km and 550 km. Multi-constellation (GPS, GLONASS, and GALILEO) observations and Swarm C satellite data over the Indian equatorial ionization anomaly (EIA) sector showed quasi-periodic oscillations in the total electron content (TEC) and amplitude scintillations resulting from the IGWs of Tonga explosion.